2013
DOI: 10.1021/ma401431h
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light-Induced Grafting from Polyolefins

Abstract: Polyethylene-graft-poly(tert-butylacrylate) (PE-g-PtBA) copolymers were prepared by using a combination of ring-opening metathesis polymerization (ROMP), hydrobromination, and visible light-induced free radical polymerization. First, cis-cyclooctene was polymerized via ROMP in the presence of a chain transfer agent and quantitatively hydrobrominated. Poly(tert-butyl acrylate) (PtBA) chains were then grown via a grafting from approach from the Br-substituted linear poly(ethylene) (PE) backbone using dimanganese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 74 publications
3
45
0
Order By: Relevance
“…Due to the absence of polar groups, semi-crystalline morphology, resistance to polar or ionic chemicals and limited chemical substitution, oxidation and free radical reactions, these modifications are quite challenging and usually are difficult to maintain [5]. There are two main modification methods in the literature: (i) direct copolymerization of either α-olefin [6,7] or polar monomers [8,9] and (ii) chemical modification of preformed polymers [10,11]. For example, antibacterial [12], antifouling [13] and hydrogen storage [14] properties of polypropylene were enhanced via surface-initiated atom transfer radical polymerization [15].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the absence of polar groups, semi-crystalline morphology, resistance to polar or ionic chemicals and limited chemical substitution, oxidation and free radical reactions, these modifications are quite challenging and usually are difficult to maintain [5]. There are two main modification methods in the literature: (i) direct copolymerization of either α-olefin [6,7] or polar monomers [8,9] and (ii) chemical modification of preformed polymers [10,11]. For example, antibacterial [12], antifouling [13] and hydrogen storage [14] properties of polypropylene were enhanced via surface-initiated atom transfer radical polymerization [15].…”
Section: Introductionmentioning
confidence: 99%
“…Its utilization as a photoactive system for the fabrication of wide range of macromolecular structures deserves intense consideration from the practical point of view [23][24][25]. We have reported that the related visible light initiating systems involving both radical and cationic modes can be applied in the synthesis of various macromolecular structures, such as telechelic polymers [26], block [27,28] and graft copolymers [29], and hyperbranched polymers [30]. Scheme 3 shows the overall uses of dimanganese decacarbonyl in macromolecular syntheses.…”
Section: Other Free Radical Photoinitiatorsmentioning
confidence: 99%
“…We have previously shown that manganese based radical generation process can successfully be employed in different modes of polymerization processes including radical promoted cationic polymerization (51), mechanistic transformation (52,53), radical coupling (54), hyper-branching (55) and grafting from polyolefines (56). Recent studies from our laboratory showed that this chemistry can be used as a photoredox catalyst system for the ATRP of vinyl monomers such as methyl methacrylate, methyl acrylate and styrene (57).…”
Section: Visible Light-induced Atrp By Using Dimanganese Decacarbonylmentioning
confidence: 99%